2021 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW) 2021
DOI: 10.1109/vrw52623.2021.00106
|View full text |Cite
|
Sign up to set email alerts
|

CAVE vs. HMD in Distance Perception

Abstract: This study aims to analyze differences between a CAVE system and a Head-Mounted Display (HMD), two technologies presenting important differences, focusing on distance perception, as past research on this factor is usually carried with only one or the other device. We performed two experiments. First, we explored the impact of the HMD's weight, by removing any other bias. Second, we compared distance perception using a simple hand interaction in a replicated environment. Results reveal that the HMD's weight has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…CAVE iVR was favored in a few early studies because of higher reported levels of presence and stronger emotional responses in subjects, 96 , 97 whereas others found that participants rated HMD higher in terms of presence and showed better task performance 98 , 99 . Some studies suggested a minimal difference between the two systems regarding user attention, engagement, and comfort 95 , 100 , 101 . These inconsistencies might be partly attributed to the continuous evolution of iVR technologies, particularly the HMDs, which can dramatically impact user experiences.…”
Section: Discussionmentioning
confidence: 99%
“…CAVE iVR was favored in a few early studies because of higher reported levels of presence and stronger emotional responses in subjects, 96 , 97 whereas others found that participants rated HMD higher in terms of presence and showed better task performance 98 , 99 . Some studies suggested a minimal difference between the two systems regarding user attention, engagement, and comfort 95 , 100 , 101 . These inconsistencies might be partly attributed to the continuous evolution of iVR technologies, particularly the HMDs, which can dramatically impact user experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Many research activities have focused on virtual environments with cave like systems, where the user still sees his own body parts as well as the evaluated feedback devices (Giri et al, 2021). Nowadays, head mounted displays (HMDs) are increasingly represented, due to their expansion within the consumer market (Combe et al, 2021).This offers new possibilities for haptic feedback systems, because the user does not necessarily see any real surrounding. This article describes a tool replica which allows to simulate several hand-held tools.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the advent of HMD (head-mounted display), VR began to be used in large numbers in all walks of life for professional use and in every household for personal use [1]. Many researches are interested in the difference in terms of visual perception in the two types of devices [2]. Another reason is the diversity and low cost of 3D application development platforms such as Unity3D, Unreal Engine, etc.…”
Section: Introductionmentioning
confidence: 99%